The effect of role conflict on academic burnout of undergraduate Economics students - Kristina, Ayu Dina; Loekmono, J.T. Lobby; Setyorini, Setyorini (Universitas Negeri Padang, 2020)
Role conflict is experienced by students when incompatible demands relatively rated to a set of standards or conditions that influence their role performance. When students continuously experience role conflict, it leads to academic burnout. Therefore, this research aims to determine the significant effect of role conflict on academic burnout of undergraduate economics students. This is a quantitative research, with data obtained from a total of 114 undergraduate economics students consisting of 29% males and 71% females using the Role Questionnaire (Rizzo et al., 1970) and Maslach Burnout Inventory Student Survey (MBI-SS) (Schaufeli et al., 2002). The result of simple linear regression analysis showed that the values of βand sig. are 0.023 and 0.343 (>0.05), which means that the effect of role conflict on academic burnout among students is insignificant.